Apalachee Crapemyrtle—Lagerstroemia indica × fauriei ‘Apalachee’ - Gary W. Knox (EDIS, 2014)
‘Apalachee’ crapemyrtle is a small deciduous tree with lavender flowers, dark green leaves, and cinnamon-orange bark. Lagerstroemia indica x fauriei ‘Apalachee’ is one of the hybrids released in 1987 from the breeding program of the U.S. National Arboretum. It grows as an upright to vase-shaped multi-stemmed tree in USDA Cold Hardiness Zones 7a-9b. This 2-page fact sheet was written by Gary W. Knox and published by the UF Department of Environmental Horticulture, December 2013.